2011
DOI: 10.1002/bjs.7669
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of survival and disease recurrence after radiofrequency ablation for hepatocellular carcinoma

Abstract: RFA provides a valuable treatment option for patients with unresectable HCC. It improves survival in those previously considered to have advanced disease. As progress continues to be made, RFA is gradually being used to treat resectable HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
162
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(175 citation statements)
references
References 94 publications
5
162
1
4
Order By: Relevance
“…Both systematic reviews 37 and recent publications 38 have highlighted the fact that resection produces better results than RFA especially in small HCC. However, the advantage of RFA is the lack of post-procedure adhesions which may result from surgery which provides greater technical ease in explantation during salvage transplantation.…”
Section: Resection Versus Ablationmentioning
confidence: 99%
“…Both systematic reviews 37 and recent publications 38 have highlighted the fact that resection produces better results than RFA especially in small HCC. However, the advantage of RFA is the lack of post-procedure adhesions which may result from surgery which provides greater technical ease in explantation during salvage transplantation.…”
Section: Resection Versus Ablationmentioning
confidence: 99%
“…A major drawback of RFA is the high rate of tumor recurrence after the therapeutic procedure, which affects the patient survival and is the main reason why RFA is considered to be inferior to surgical resection in cases of resectable lesions [5]. In the aforementioned study from Korea, Kim et al demonstrated the 5 and 10 year cumulative local tumor recurrence rates to be 27.0 % and 36.9 % respectively, with 5 and 10 year cumulative intrahepatic distant and extrahepatic recurrence rates of 73.1 %/ 88.5 % and 19.1 %/ 38.2 % respectively [2].…”
Section: Editorialmentioning
confidence: 99%
“…The algorithm of the National Comprehensive Cancer Network guideline states that RFA is categorized as locoregional therapy, and tumors ≤3 cm are optimally treated with RFA [3]. Recent developments in RFA technology have made it possible to necrotize a large volume of tissue (≥3 cm in diameter) [4,5]. RFA was reported to be relatively safe, with a mortality rate of 0.3% [6].…”
Section: Introductionmentioning
confidence: 99%